2005
DOI: 10.1007/s11663-005-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thiourea during nickel electrodeposition from acidic sulfate solutions

Abstract: The effect of thiourea on the cathodic current efficiency (CE), deposit quality, crystallographic orientations, surface morphology, and polarization behavior of the cathode was investigated during nickel electrodeposition from acidic sulfate solutions for 2 hours at 60 °C. A slight decrease of 3 to 4 pct in the CE was observed, when the concentration of thiourea was increased from 2 to 40 mg dm Ϫ3 . The nickel deposit quality deteriorated significantly at higher thiourea concentrations; the surface morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…20 The characteristic reduction potential for such TU decomposition to sulfide ion has been attributed to a voltammetric wave near −0.7 V vs SCE. 17 A similar reduction wave is evident in Fig. 4 for the S-containing depolarizing additives with the wave peak approximately at −0.75 V for TU, −0.72 V for SPS, −0.71 V As the overpotential increases the depolarizing effects of the additives diminish; TU and SPS actually begin to inhibit the nickel deposition rate at potentials below −0.92 V. A similar potentialdependent transition in TU behavior from acceleration to inhibition was also recently reported.…”
Section: D444mentioning
confidence: 99%
See 2 more Smart Citations
“…20 The characteristic reduction potential for such TU decomposition to sulfide ion has been attributed to a voltammetric wave near −0.7 V vs SCE. 17 A similar reduction wave is evident in Fig. 4 for the S-containing depolarizing additives with the wave peak approximately at −0.75 V for TU, −0.72 V for SPS, −0.71 V As the overpotential increases the depolarizing effects of the additives diminish; TU and SPS actually begin to inhibit the nickel deposition rate at potentials below −0.92 V. A similar potentialdependent transition in TU behavior from acceleration to inhibition was also recently reported.…”
Section: D444mentioning
confidence: 99%
“…As a point of departure the effects of prototypical cationic, anionic, and nonionic surfactants on the nickel deposition were examined. The survey is far from exhaustive, and the molecules examined were largely selected from prior reports of conventional Ni leveling [11][12][13][14][15][16][17][18][19][20][21][22][23] as well as Cu electroplating and superfilling. [23][24][25][26][27][28][29][30] Experimental Ni electrodeposition was studied using a variant of a Watts bath composed of 1 mol/L NiSO 4 ·6H 2 O, 0.2 mol/L NiCl 2 ·6H 2 O, and 0.5 mol/L H 3 BO 3 dissolved in 18 M⍀ cm deionized water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This typical morphological appearance of nickel deposition was also reported by various researchers. [13][14][15][16][17][18] Although these researchers employed varied techniques and parameters, they arrived at the same morphological patterns.…”
Section: Microscopic Analysismentioning
confidence: 99%
“…Mohanty et al 17 stated that the nickel deposition with dominant plane (111) produced more condensed nickel layer compared to other planes. Chao-qun et al 27 also reported the deposition of the (111) plane in their work.…”
Section: Effect Of Current Density On Coating Hardnessmentioning
confidence: 99%